Ácidos orgânicos e seus sais e nisina no controle de bactérias láticas, aeróbias mesófilas e listeria monocytogenes em salsichas - Zdanski, Scheila Fernanda Rockembach (2011)
The sausage is a product of high consumption, but due to its manufacturing process technology, it becomes susceptible to microbiological contamination. To ensure the life of the sausage and their microbiological safety, means of minimizing contamination levels, limiting or preventing microbial growth. Therefore, the objective of this study was to add antimicrobials in the formulation and post-heat treatment, and evaluate their effects on growth of mesophilic aerobic bacteria, lactic acid bacteria and Listeria monocytogenes in sausages vacuum packed, stored at 5 º C during storage of 35 days. We evaluated four treatments: (T1-2.5% solution of sodium lactate in the formulation and immersion in 200 mg / l of nisin solution, T2 - 2.5% solution of sodium lactate in the formulation and immersion 200 mg / l of nisin solution followed by 2.5% solution of lactic acid, T3 - 2.5% solution of potassium lactate and sodium diacetate in formulation and immersion in 200 mg / l of nisin solution; T4-2.5% solution of potassium lactate and sodium diacetate in formulation and immersion in 200 mg / l of nisin solution followed by 2.5% lactic acid solution) and a control (no antimicrobial was added in formulation and post-thermal processing). There were microbiological (lactic acid bacteria, aerobic mesophilic, and Listeria monocytogenes) and physico-chemical (pH). At the end of 35 days storage there was a synergy between antimicrobials used in the formulation and post-heat treatment, reducing the total count of mesophilic and lactic acid bacteria, as compared to control, and the (T4), who used the formulating a mixture of potassium lactate and sodium diacetate, with the subsequent nisin followed by immersion in lactic acid more effective. The treatments that were used nisin (T1 e T3), after the heat treatment, were not effective in controlling aerobic mesophilic and lactic acid bacteria. Listeria monocytogenes was identified in all control samples during the 35 days of storage. Thus, the synergistic action of antibiotics added to the formulation, and post-thermal processing are obstacles that had a potential to control the growth of mesophilic aerobic bacteria and lactic acid bacteria and especially able to inhibit the growth of Listeria monocytogenes in vacuum-packed sausages and stored at 5 ° C for 35 days of storage.